Subnational fiscal sustainability analysis : what can we learn from Tamil Nadu ? - Ianchovichina, Elena 2000- (Policy research working paper, 2006)
"In the late 1990s the Indian state of Tamil Nadu experienced an unprecedented fiscal deterioration, which was part of the widespread fiscal deterioration in Indian states. This deterioration was troubling because current expenditure outgrew total revenue, leaving little fiscal space for infrastructure spending. The paper presents a framework for subnational fiscal sustainability analysis and applies it to Tamil Nadu where subsequent fiscal adjustment has been ambitious and politically challenging, but has promised to put state finance on a sustainable path and create fiscal space for infrastructure investment. The paper emphasizes the differences between fiscal sustainability analysis at the national and subnational levels, attempts to take into account uncertainty, and discusses the key components of the state's fiscal accounts and how they respond to reforms and shocks. Risks to Tamil Nadu's fiscal outlook include interest rate shocks, pressures on the primary balance, and contingent liabilities. Though the state's efforts to remove constraints to economic growth, minimize recurrent expenditures and maximize its revenue potential will be critical for fiscal sustainability, national policies feature prominently in subnational fiscal adjustment. Tamil Nadu's quest for fiscal sustainability is relevant for other countries. Decentralization has given subnational governments in developing countries significant spending and taxation responsibilities, and the capacity to incur debt. The fiscal stress of the Indian states echoed the fiscal crises of subnational governments in several other major emerging economies. "--World Bank web site